Diatom assemblage changes in lacustrine sediments from Isla de los Estados, southernmost South America, in response to shifts in the southwesterly wind belt - Fernández, Marilén; Björck, Svante; Wohlfarth, Barbaria; Maidana, Nora Irene; Unkel, Ingmar; Van der Putten, Nathalie (Journal of Paleolimnology)
Isla de los Estados (54° 45′S, 63° 10′–64° 46′W) lies east of the main island of Tierra del Fuego and is the southeastern-most point in Argentina. Because of its geographic position near the latitudes of the Southern Hemisphere Westerlies and the strong influence of the Antarctic Circumpolar Current (ACC), the area is suitable for paleoecological and paleoclimate research. The island is not far north of the Subantarctic Front, which limits the northern boundary of the ACC. Paleoenvironmental study in this geographic location can shed light on past changes in atmospheric and marine circulation patterns. Diatom analysis of the lower part of a sediment sequence from Laguna Cascada (54° 45′ 51.3′′S, 64° 20′ 20.07′′W) enabled inference of changing lake conditions between 16 and 11.1 cal ka BP. Between 16 and 14.4 cal ka BP fragilarioid diatom species, often a pioneer group, dominated the record. Their presence shows seasonally open-water conditions from the onset of sedimentation. In zone II (14.4–12.8 cal ka BP), the dominance of planktonic/tychoplanktonic Aulacoseira spp. might represent longer ice-free periods and windier conditions, which would have kept this heavy species suspended in the water column. This period corresponds to the Antarctic Cold Reversal, when the Southern Hemisphere Westerlies were possibly centered on the latitudes of Tierra del Fuego, resulting in windy and wet conditions. Zone III (12.8–11.1 cal ka BP) is dominated by benthic diatom taxa that are mainly associated with peat and wetland vegetation. This suggests that climate conditions had become milder and less windy, favoring aquatic productivity and terrestrial vegetation development. This change in environmental conditions may have been a consequence of the southward movement of the Southern Hemisphere Westerlies at the start of the Antarctic Holocene thermal optimum. Fil: Fernández, Marilén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Björck, Svante. Lund ...